KONSEP DASAR EVALUASI DAN IMPLIKASINYA DALAM EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Hidayat, Tatang; Asyafah, Abas (Universitas Islam Negeri Raden Intan Lampung, 2019)
This paper aims to discover the basic concepts of evaluation and its implications on evaluating Islamic Religious Education learning in Schools. This paper employs a qualitative approach and literature study method. Based on the results of the discussion, the evaluation consisted of measurement and assessment. In the context of learning, evaluation has a very important and strategic position since it is included in the steps of learning. The aim is to determine the effectiveness and efficiency of the learning system. The area of discussion includes evaluation in learning programs, learning processes, and learning outcomes. In general, the principle of evaluation consists of continuity, comprehensiveness, fairness, objectivity, cooperativeness, and practicality. In specific, the principle consists of integration, coherence, pedagogical, and accountability. In terms of type, learning evaluation consists of evaluation of planning, development, monitoring, impact, efficiency, and comprehensive programs. In terms of object, evaluation of learning includes input, transformation, and output. The subject includes the educator, the officer who has been trained, and the students that can evaluate themselves. In terms of the technique, it consists of tests and non-tests. The implication is that the evaluation of the learning of Islamic Religious Education in schools needs to be carried out in a continuous, comprehensive and integrated manner. Thus, Islamic Religious Education educators must be able to evaluate the development of students, including in the aspects of aqliyah, qolbiyah, and amāliyah.